CTNI-44. INTERIM RESULTS OF PHASE 2 STUDY TO EVALUATE PI3K/mTOR INHIBITOR PAXALISIB (GDC-0084) GIVEN TO NEWLY DIAGNOSED GLIOBLASTOMA PATIENTS WITH UNMETHYLATED O6-METHYLGUANINE-METHYLTRANSFERASE PROMOTER. (9th November 2020) - Wen, Patrick; de Groot, John; Battiste, James; Goldlust, Samuel; Damek, Denise; Garner, James; Simpson, Jeremy; Olivero, Alan; Cloughesy, Timothy
Abstract: BACKGROUND: Paxalisib (GDC-0084) is a potent, oral, selective small molecule inhibitor of class I phosphoinositide 3-kinase and mammalian target of rapamycin (PI3K/mTOR). Paxalisib crosses the blood-brain barrier and achieves a brain / plasma ratio of approximately 1.0. An MTD of 60mg per day has been identified in newly diagnosed glioblastoma (GBM) patient with unmethylated O6 -methylguanine-methyltransferase (MGMT) promotor status. Paxalisib has shown encouraging indications of clinical activity. METHODS: This study has a 2-part design: an open-label, dose-escalation phase (Stage 1) to define MTD, followed by an expansion cohort (Stage 2) at the MTD and patients are randomized to take paxalisib, in fed or fasted states. Pharmacokinetic data will be analysed and compared by dose and fed/fasted status. RESULTS: Stage 2 (expansion cohort) is fully enrolled and patients are in follow-up. Adverse event profile seems broadly consistent with prior clinical experience and with other PI3K-targeting agents. With analysis including all patients, a sustained PFS signal of 8.5 months is seen and this compares favourably with historical controls. CONCLUSION: Paxalisib displays a safety profile consistent with previous data and promising efficacy signals in newly diagnosed GBM. A pivotal study in GBM is planned to commence recruitment later this year.